Analysis of Problem Solving Ability and Independent Learning Based On IT-Assisted PBL At Nurul Azizi Integrated Islamic Middle School - Siregar, Muhammad Fadhil Hidayat; Hasratuddin, Hasratuddin; Sitompul, Pardomuan (Universitas Wiralodra, 2024)
This research is crucial since students struggle with math. They want to